Model-driven engineering and software development : third International Conference, MODELSWARD 2015, Angers, France, February 9-11, 2015, Revised selected papers /: third International Conference, MODELSWARD 2015, Angers, France, February 9-11, 2015, Revised selected papers. (2015) - Unknown
No abstract available